Improved Output Voltage Quality using Space Vector Modulation for Multilevel Inverters - Auzani Jidin; Syamim Sanusi; Tole Sutikno; Nik Rumzi Nik Idris (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Space vector modulation (SVM) has received wide acceptance due to many benefits over other techniques such as higher output voltages, lower total harmonic distortion (THD), high-efficiency and flexible to be implemented in vector control systems. In digital implementation, the SVM equations can be optimally computed by eliminate the use of complex forms. In this paper, the simple SVM based on two-level inverter is employed for higher levels of inverters. This is to retain the simplicity of SVM computation for three-level and five-level cascaded H-bridge multilevel inverter (CHMI). Moreover, the proposed method utilizes two controller boards to perform high computational workloads and to eliminate glitch and error problems. Experiment results show that the THD of output voltage in five-level CHMI gives the smallest value among the results obtained from other levels.